Impact of a fall prevention education program for health and exercise professionals: a randomised controlled trial - Anne Tiedemann; Daina L Sturnieks; Anne-Marie Hill; Lorraine Lovitt; Lindy Clemson; Stephen R Lord; Catherine Sherrington (Public Health Research & Practice, 2021)
Objectives and importance of study: Exercise prevents falls among community-dwelling older adults. Therefore, it is crucial that health and exercise professionals have the knowledge and skills to prescribe appropriate fall prevention exercise. This study evaluated the effect of a fall prevention education program, compared with a waitlist control group, on health and exercise professionals’ fall prevention knowledge and behaviour, and their confidence to prescribe fall prevention exercises for older people.